2016
DOI: 10.1073/pnas.1522748113
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and matching TREK/TRAAK subunits generate heterodimeric K 2P channels with unique properties

Abstract: The tandem of pore domain in a weak inwardly rectifying K + channel (Twik)-related acid-arachidonic activated K + channel (TRAAK) and Twikrelated K + channels (TREK) 1 and TREK2 are active as homodimers gated by stretch, fatty acids, pH, and G protein-coupled receptors. These two-pore domain potassium (K 2P ) channels are broadly expressed in the nervous system where they control excitability. TREK/TRAAK KO mice display altered phenotypes related to nociception, neuroprotection afforded by polyunsaturated fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 41 publications
6
76
0
Order By: Relevance
“…We have previously described that RR inhibits background K 1 currents in DRG neurons (Braun et al, 2015). The molecular correlates of the RRsensitive K 1 current may be TREK-2, TASK-3, or TRAAK homodimers, or heterodimers of the TREK subfamily (Braun et al, 2015;Blin et al, 2016;Lengyel et al, 2016). We found that in neurons derived from wild-type animals, A2764 strongly inhibited the background K 1 current in a subset of DRG neurons.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously described that RR inhibits background K 1 currents in DRG neurons (Braun et al, 2015). The molecular correlates of the RRsensitive K 1 current may be TREK-2, TASK-3, or TRAAK homodimers, or heterodimers of the TREK subfamily (Braun et al, 2015;Blin et al, 2016;Lengyel et al, 2016). We found that in neurons derived from wild-type animals, A2764 strongly inhibited the background K 1 current in a subset of DRG neurons.…”
Section: Discussionmentioning
confidence: 59%
“…Note Added in Proof-While this paper was under review, other authors have published results showing heteromerization of channels in the TREK K 2P subfamily (38,39). These studies reached the same conclusion by using different methods.…”
Section: Acknowledgments-the Skillful Technical Assistance Of Irén Vementioning
confidence: 69%
“…Kim (2003) reviewed the main characteristics of the modulation of two-pore domain K + channels by FFA (TREK-1, TREK-2, and TRAAK). These channels, activated by GPCRs, stretch, pH, and PUFA, are broadly expressed in the nervous system where they control neuronal excitability (Lee et al, 2011; Liu et al, 2014; Blin et al, 2016). The effect of PUFA on TREK channels has profound physiological implications, since TREK-1 was shown to mediate the neuroprotection induced by PUFA (Lauritzen et al, 2000; Heurteaux et al, 2004; Noël et al, 2011; Liu et al, 2014).…”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 99%